Deal or no deal: U.S. homeowners’ willingness to pay for residential building retrofits - Zachary Berzolla; Ting Meng; Christoph Reinhart (Environmental Research: Infrastructure and Sustainability)
With buildings accounting for nearly 40% of global carbon emissions, deep energy retrofits to reduce emissions in the majority of existing buildings are necessary to meet global climate goals. Yet a deep retrofit can easily cost $50 000 or more, limiting its affordability and thus likelihood of adoption for many households. This paper presents a model of homeowners willingness to pay for different retrofits. The model is meant to quantify the willingness of homeowners to make the economic decision to upgrade their buildings. It can be used to inform the required subsidies to catalyze adoption across the socio-economic spectrum and thus achieve emissions reduction goals. The model is based on a survey of 1200 homeowners in the Northeastern U.S. A logistic regression is carried out on whether or not a respondent is willing to pay for a retrofit. The predictor variables are based on the socioeconomic factors asked in the survey. Key factors influencing homeowners’ willingness to pay include the upfront cost, their income, and their concern about emissions from their home. Notably, increasing concern about emissions for all respondents from the median of ‘slightly concerned’ to ‘extremely concerned’ led to a 50% savings in retrofit subsidy cost. The model can help jurisdictions throughout the U.S. better allocate limited resources to catalyze higher adoption rates of building retrofits.